A multi-scale model for the tensile failure of twill textile composites. (1st March 2023) - Kheng, Eugene; D'Mello, Royan; Waas, Anthony
Abstract: Results for the tensile deformation response of a twill woven textile composite are presented, where both the mesostructure and the microstructure of the textile are seen to influence the response. In particular twill composites can exhibit differences in mechanical response that are dependent on the location and size of a notch of dimensions that are comparable to the tow mesostructure. A multi-scale mechanical model is developed and used to explain the differences in deformation response. We show that the evolution of mesoscale damage can accurately be modeled by including features of the mesoscale architecture. Graphical abstract: Highlights: Static tensile tests of notched twill composite show overall toughness dependence on placement of notch relative to mesoscale structure. Computational multiscale modeling can accurately reproduce the toughness dependence and failure mechanisms.